Comparative Effects of Preoperative Carbohydrate Loading And Fasting on Recovery Outcomes in Colorectal Surgery: Carbohydrate Loading and Fasting in Colorectal Surgery - Mureed, Ayesha; Dian, Asifa; Shafique, Umer; Zia, Kanwal; Ahmad, Zeeshan; Sattar, Abdul (Pakistan Journal of Health Sciences, 2024)
Preoperative oral carbohydrate treatment improves postoperative recovery. Fasting before surgery increases stress response and insulin resistance. Objective: To examine the effects of preoperative oral carbohydrate loading and traditional fasting on gastrointestinal function, independent walking time, and hospital stay after colorectal surgery. Methods: A quasi-experiment study with 90 individuals diagnosed by extensive history, clinical examination, and pertinent investigations split patients into Group A and Group B. General Anesthesia was used for all surgeries. Group A had surgery after 6 hours of nil per os, whereas Group B had a clear carbohydrate drink 14 hours before surgery and another 2 hours before anesthesia induction. Up to 72 hours after surgery, bowel noises, first flatus and feces, and time to independent ambulation were monitored. Results: The conventional approach in Group A produced a mean time of 51.4 ± 5.2 hours for bowel sounds, 62.9 ± 6.5 hours for first flatus, 77.95 ± 1.00 hours for defecation, 82.73 ± 9.6 hours for independent ambulation, and 5.02 ± 1.4 days for hospital stay. Group B, who received oral carbohydrate loading therapy before surgery, had shorter times for bowel sounds (43.5 ± 9.1 hours), first flatus (54.8 ± 4.6 hours), defecation (67.5 ± 11 hours), and independent ambulation (72.7 ± 6.6 hours), but a similar hospital stay (5.02 ± 1.49 days Hospital stay was not substantially different (p-value = 0.744), but surgical results were (0.000). Conclusions: Oral carbohydrate loading before colorectal surgery improves gastrointestinal function, speeds independent walking, and reduces hospital stays.